An exploration of the role of transformational leadership in times of institutionalization of change - Ursula El-Hage; Dina Sidani (Universidad de Deusto, 2023)
In order to adapt to an increasingly competitive world, organizations need to continuously change, yet the success of the change is conditioned by its institutionalization. The institutionalization of change is the key factor to perpetuate sustainable changes. Based on the exploration of the role of transformational leadership in times of (institutionalization of) change, the objective of this study is to analyze the contribution of the components of transformational leadership on the institutionalization of change within a Lebanese private university Redundancy, engaged in an accreditation process. Through a qualitative method on a single case study, based on semi-structured interviews conducted with 15 senior executives occupying key positions in the studied university and through 15 focus groups with 85 faculty members from four disciplinary fields, we explored the role of each of the four dimensions of transformational leadership in times of institutionalization of change. Our findings highlight the essential role of intellectual stimulation and inspirational motivation of transformational leadership, while the two other dimensions, idealized influence and individualized consideration, play a limited role in the university context of institutionalization of change. Moreover, individual recognition and idealized influence are essential to convince all members of the need for change and involve them in the accreditation process. This study allows us to understand the role of each of the transformational leadership dimensions in order to promote and escort institutionalization of change within high education sector. Received: 16 June 2021 Accepted: 20 June 2023